Prognostic impact of the tumor-infiltrating regulatory T-cell (Foxp3(+))/activated cytotoxic T lymphocyte (granzyme B(+)) ratio on resected left-sided pancreatic cancer - Hwang, Ho Kyoung (Oncol Lett, 2016)
Among the subsets of tumor-infiltrating lymphocytes (TILs), activated cytotoxic T lymphocytes (granzyme B(+)) have an antitumor effect, while regulatory T lymphocytes [forkhead box P3 (Foxp3)(+)] suppress the antitumor immune response. The aim of the present study was to investigate the possible associations between TIL subsets and survival outcomes in patients with left-sided pancreatic ductal adenocarcinoma (PDAC). From January 2000 to December 2008, 30 patients who underwent curative distal pancreatectomy without neoadjuvant chemoradiotherapy due to left-sided PDAC were enrolled in the present study. TIL subsets were enumerated by immunohistochemical staining for cluster of differentiation (CD)3, CD4, CD8, Foxp3 and granzyme B in the intra-tumoral areas of tissue blocks. Patients were divided into two groups according to the median value of the absolute counts and relative ratios of TIL subsets. In the univariate analysis, age, gender, tumor size, nodal stage, tumor differentiation and lymphovascular/perineural invasion were not significantly associated with survival outcome. However, low levels of preoperative cancer antigen (CA) 19–9 were associated with a longer overall survival (OS), although the association was not significant (37 vs. 18 months; P=0.061). A high level of granzyme B(+) was associated with enhanced disease-free survival (DFS) (25 vs. 10 months; P=0.023), and a low Foxp3(+)/granzyme B(+) ratio was associated with a favorable prognosis in terms of DFS (25 vs. 8 months; P=0.008) and OS (47 vs. 17 months; P=0.003). In the multivariate analysis, the ratio of Foxp3(+)/granzyme B(+) was an independent prognostic factor for determining DFS [Exp(B), 3.060; 95% confidence interval (CI), 1.259–47.436; P=0.014] and OS [Exp(B), 3.580; 95% CI, 1.460–8.780; P=0.005]. Among the clinicopathological factors, low levels of CA 19–9 were significantly associated with a low Foxp3(+)/granzyme B(+) ratio (P=0.016). The results of the present study suggested that a low Foxp3(+)/granzyme B(+) ratio may be useful for predicting a good prognosis in surgically resected left-sided PDAC.